Plant-Parasitic Nematodes on Sugarcane in Florida - William T. Crow (EDIS)
Plant-parasitic nematodes are microscopic roundworms that feed on and damage plants. Ectoparasitic nematodes live and reproduce in soil and feed on roots from outside. Endoparasitic nematodes enter into the roots to feed and reproduce. Sting nematode (Belonolaimus longicaudatus), an ectoparasite, is the most damaging nematode to sugarcane in Florida. This document is ENY-053, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: September 2004.